2021
DOI: 10.1016/j.diabres.2021.108925
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for COVID-19 hospitalisation and death in people living with diabetes: A virtual cohort study from the Western Cape Province, South Africa

Abstract: Background COVID-19 outcomes and risk factors, including comorbidities and medication regimens, in people living with diabetes (PLWD) are poorly defined for low- and middle-income countries. Methods The Provincial Health Data Centre (Western Cape, South Africa) is a health information exchange collating patient-level routine health data for approximately 4 million public sector health care seekers. Data from COVID-19 patients diagnosed between March and July 2020, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…Metformin is contraindicated for patients with diabetes having comorbidities such as chronic kidney disease, which has a high risk for mortality. Therefore, metforminusable patients have a lower diabetic burden [25]. The exclusion of this group in our study provided a more accurate interpretation of the metformin effect.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Metformin is contraindicated for patients with diabetes having comorbidities such as chronic kidney disease, which has a high risk for mortality. Therefore, metforminusable patients have a lower diabetic burden [25]. The exclusion of this group in our study provided a more accurate interpretation of the metformin effect.…”
Section: Discussionmentioning
confidence: 87%
“…After PSM, 120 MF( +) and 120 MF( −) patients were matched. ALT values (median(IQR)) of the MF ( +) group were higher than those of the MF (-) group (25(16-42) vs 19 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), p = 0.003). ICU admission rates, in-hospital mortality rates, and postdischarge mortality rates were higher in the MF( −) group, though not significant.…”
Section: Analysis Of Data After Psm (Matched)mentioning
confidence: 88%
“…All studies evaluated data from retrospective patient cohorts, except for four (9.3%) that collected the information prospectively [ 39 , 40 , 56 , 69 ]. Six (14.0%) studies reported population-based data [ 35 , 36 , 42 , 52 , 59 , 62 ], while the others were conducted in a hospital setting. Two (4.7%) studies also included COVID-19 patients based on high clinical or radiological suspicion [ 39 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…There was substantial heterogeneity between the studies ( I 2 94.7%). Baujat’s plot suggested that three studies unduly influenced heterogeneity as well as pooled estimates ( S1 Fig ) [ 36 , 59 , 62 ]. Omitting these three studies from meta-analysis resulted in a slightly higher summary estimate of proportion (1.15%, 95% CI 0.84%-1.50%) with only a minor reduction in heterogeneity ( I 2 86.9%).…”
Section: Resultsmentioning
confidence: 99%
“…The exceptionally high proportion of poorly controlled and newly diagnosed diabetics in our sample could explain the increased susceptibility of the population of Cape Town to the morbidity and mortality associated with COVID-19. 20 …”
Section: Discussionmentioning
confidence: 99%